EFFECT OF 2,4-D ON PHENOLICS PRODUCTION AND DETECTION OF INVITRO CULTURE-INDUCED VARIATION THROUGH INTER-SIMPLE SEQUENCE REPEAT AND RAPD ANALYSIS IN ARTEMISIA ANNUA L. - KRISHNA KUMAR RAI; NEHAPANDEY; SHASHI PANDEY-RAI (International Journal of Pharma and Bio Sciences, 2014)
In the present study, the effect of 2,4-dichlorophenoxyacetic acid (2,4-D) on callus cultures of Artemisia annua were evaluated in terms of its growth, chlorophyll, carotenoid, protein, phenol and flavonoid content and possible genetic variations using ISSR and RAPD markers. Callus cultures grown on MS medium supplemented with three different 2,4-D concentration (1.0, 2.0 and 3.0 mg 2,4-D L-1 MS medium) showed significant alterations in terms of callogenesis and growth. Callus grown on MS + 3.0 mgL-1 2,4-D was found to impose highest degree of alterations and the callus width as well as the dry weight of 25 days old callus was highest at MS + 3.0 mgL-1 2,4-D. Chlorophyll, carotenoid and flavonoid showed an increment in dose dependent manner while protein and phenol content declined as the concentration of 2,4-D increased in the medium. Investigations focused on DNA fingerprinting analysis using RAPD and ISSR markers showed genetic variations induced by high concentration of 2,4-D. Out of 31 markers used in this study, markers UBC-823, UBC-886, UBC-840, UBC-895 and OPE7 showed polymorphism above 50%. These five markers showed their potential role in detection of genetic variability induced by high concentration of 2,4-D under in-vitro condition at an early stage and the maximum polymorphism was found in callus grown in highest concentration of 2,4-D i.e. MS + 3.0mgL-1 2,4-D. Our results clearly demonstrated that in A. annua use of 2,4-D for callus generation above the concentration of 2.0 mgL-1 medium, may induce genetic variations and thus should be avoided where the need of generation of genetically alike callus/plantlets is desired.